2015
DOI: 10.1007/s00431-015-2526-4
|View full text |Cite
|
Sign up to set email alerts
|

Different antibiotic strategies in transient tachypnea of the newborn: an ambispective cohort study

Abstract: • Our combined strategy for TTN can reduce antibiotics usage. • New strategy did not increase the incidence of infection and adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In contrast, Weintraub et al reported no difference in median length of hospital stay between the treated and untreated groups. Similarly, in 2015, Li et al reported no difference between the control and treated groups [17,18].…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, Weintraub et al reported no difference in median length of hospital stay between the treated and untreated groups. Similarly, in 2015, Li et al reported no difference between the control and treated groups [17,18].…”
Section: Discussionmentioning
confidence: 92%
“…Twenty studies were identified that described aspects of guideline implementation or health systems strengthening to improve outcomes of preterm babies in LMICs [ 59 , 63 , 104 , 128 , 130 , 135 , 142 , 144 , 145 , 157 , 177 , 178 , 180 , 181 , 188 , 191 , 197 - 200 ].…”
Section: Resultsmentioning
confidence: 99%